Therapeutic Delay and Biologic Response in Hidradenitis Suppurativa: A Real-World Cohort Study - Gencebay G.; Yücesoy S. N.; DİZMAN D.; Yetimova N. Ç.; Tak A. Y.; Küçük Ö. S. (My University, 2026)
Background: Hidradenitis suppurativa (HS) is a chronic inflammatory disease with a progressive course that may lead to scarring and impaired quality of life. Early initiation of biologic therapy has been proposed to improve outcomes; however, real-world evidence remains limited. Objectives: To assess treatment outcomes of patients with HS in a tertiary care center, with a particular focus on the effect of treatment delay and the potential association between early biologic therapy and clinical response, evaluating the concept of a therapeutic \"window of opportunity\" in an observational real-world study. Methods: This retrospective cohort included 152 patients with HS treated between December 2022 and March 2025. Disease severity was assessed using the International Hidradenitis Suppurativa Severity Score System (IHS4) and Hurley stage. Patients were stratified by treatment type (biologic vs. nonbiologic). Demographic characteristics and comorbidities were systematically recorded. Statistical analyses included Mann–Whitney U tests, Wilcoxon signed-rank tests, Spearman correlation, and Cox regression to evaluate treatment delay as a predictor of response. Results: Among 152 patients (71.1% male; mean age: 35.9 ± 12.2 years), 88 (57.9%) received biologic therapy. Patients treated with biologics presented with significantly more severe disease (mean IHS4: 13.7 ± 7.9 vs. 3.8 ± 4.4; p < 0.001) and achieved greater absolute improvement (ΔIHS4: −7.6 ± 9.0 vs. −2.2 ± 5.0; p < 0.001). Cox regression demonstrated that therapeutic delay inversely predicted response (p = 0.045). Hurley stage strongly correlated with IHS4 (Spearman r = 0.904; p < 0.001). Male patients represented 83.0% of the biologic therapy group compared to 54.7% in the nonbiologic group (p < 0.001). Smoking prevalence was 75% but did not significantly affect treatment response. Conclusions: Earlier initiation of biologic therapy may be associated with greater clinical improvement in HS; however, this finding should be interpreted with caution due to the retrospective design, baseline imbalances, and potential confounding. The concept of a therapeutic \"window of opportunity\" remains hypothesis-generating and requires confirmation in prospective studies with standardized outcome measures.
Keywords: Tıp; Dahili Tıp Bilimleri; Dermatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Dermatology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Clinical Medicine (Med); Clinical Medicine; biologic therapy; comorbidities; hidradenitis suppurativa; therapeutic delay; window of opportunity